THE ISLAMIC TRADITION OF BAKUMPAI DAYAK PEOPLE - Nasrullah Nasrullah (Graduate Program of Pontianak Institute of Islamic Studies, 2014)
This paper presents the dilemma of an ethnic group which is influenced by the views from the outside as well as the inside with regard to the dominance of religious identity. Specifically, this paper discusses the existence of Bakumpai and the Bakumpai people as part of the Dayak tribes and their Islamic practice. This article is expected to provide understanding of religious diversity in an ethnic group particularly the Dayak and how it influences the Dayak culture. Keywords: Bakumpai, Dayak, Islamic Tradition